Carcinogenic and health risk assessment of respiratory exposure to acrylonitrile, 1, 3-butadiene and styrene in the petrochemical industry using the US Environmental Protection Agency method. Issue 4 (2nd October 2022) - Ahmadi-Moshiran, Vahid; Sajedian, Ali Asghar; Soltanzadeh, Ahmad; Seifi, Fatemeh; Koobasi, Rozhin; Nikbakht, Neda; Sadeghi-Yarandi, Mohsen
Abstract : Objectives . This study aimed to assess carcinogenic and health risks of respiratory exposure to acrylonitrile, 1, 3-butadiene and styrene (ABS) in the petrochemical industry. Methods . This cross-sectional study was conducted in a petrochemical plant producing ABS copolymers. Respiratory exposure to each of acrylonitrile, 1, 3-butadiene and styrene was measured using methods No. 1604, No. 1024 and No. 1501 of the National Institute of Occupational Safety and Health (NIOSH), respectively. The US Environmental Protection Agency (USEPA) method was used to assess carcinogenic and health risks. Results. The average occupational exposure to ABS was 560.82 µg m –3 for 1, 3-butadiene, 122.8 µg m –3 for acrylonitrile and 1.92 µg m –3 for styrene. The average lifetime cancer risk in the present study was 2.71 × 10 −3 for 1, 3-butadiene, 2.1 × 10 −3 for acrylonitrile and 6.6 × 10 −3 for styrene. Also, the mean non-cancer risk (hazard quotient) among all participants for each of 1, 3-butadiene, acrylonitrile and styrene was 4.04 ± 6.93, 10.82 ± 14.76 and 0.19 ± 0.11, respectively. Conclusion. The values of carcinogenic and health risks in the majority of the subjects were within the unacceptable risk levels due to exposure to ABS vapors. Hence, corrective actions are required to protect the workers from non-cancer and cancer risks.